The Influence of ArcGIS Story Maps Learning Media on Students’ Understanding of the Geographical Location of ASEAN Countries (Quasi Experiment Grade 8 at SMPN 29 Bandung) - Agustinah, Lusi; Komalasari, Kokom; Siti Logayah, Dina (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2023)
In the current era of ICT (Information and Communication Technology) development, learning media is undergoing transformation in its application. Teachers can use ICT in the application of varied and interactive media to help increase students’ understanding of social studies materials such as ArcGIS Story Maps which can provide concrete visualization so that students will understand social studies material better. The purpose of the research was to analyze the influence of the application of ArcGIS Story Maps media about the Geographical Location of ASEAN Countries on the understanding of grade 8 students of SMPN 29 Bandung. This research uses quantitative approaches and experimental methods with quasi-experimental design, precisely non-equivalent control group design. Based on the results of the study, it was found that both in the experimental and control classes there were differences in students’ understanding in the pre-test and post-test. If the two classes are compared, then in the pre-test there is no difference in understanding between the experimental and control classes with Asymp.Sig. (2- tailed) of 0.939 > 0.05, but in the post-test there is a difference in understanding with Asymp.Sig. (2- tailed) of 0.045 < 0.05. The N-Gain value of student comprehension is 1,622 > 1, indicating that there is a difference in understanding where learning using ArcGIS Story Maps media is more able to increase student understanding than learning with interactive Power Point. Suggestions from this study, social studies teachers can develop ArcGIS Story Maps media in the social studies learning process that is tailored to learning needs.